Optimizing the Role of Village Government and Community in Empowering BUMDes in Pabuaran Village - Furqon, Eki; Gunawan, Muhammad Safaat; Mirdedi, Mirdedi (Probono and Community Service Journal, 2025)
This community service activity aims to encourage the legalization and strengthening of Village-Owned Enterprises (BUMDes) institutions in Pabuaran District, Serang Regency. Although almost all villages have formed BUMDes, most still face administrative obstacles, especially in obtaining legal entity status and Business Identification Number (NIB). Through training and legal assistance focused on village officials, village heads, village assistants, and Village Consultative Body (BPD), this activity provides technical and normative understanding regarding the process of establishing and legalizing BUMDes based on Law Number 6 of 2014 concerning Villages, Government Regulation Number 11 of 2021, and Permendesa PDTT Number 3 of 2021. The training was carried out using participatory and application methods, including simulations of filling out documents, technical consultations, and preparation of legal entity registration files. The results showed a significant increase in regulatory understanding and administrative readiness of villages in accelerating the legalization of BUMDes. As a continuation, assistance is carried out continuously by the Constitutional Law Division of the Faculty of Law, Sultan Ageng Tirtayasa University through direct consultation services on campus.